Hardware and software development for computerised harmonics measurement / Jamaludin Othman - Othman, Jamaludin (1996)
This project is to develop The hardware and software part of a Computerised Harmonics Measurement employing a High Performance Data Acquisition Card (PCL-818H). The works involved are calibrating and programming for current operation of the card and detecting, amplifying and filtering of signals to be analysed. The programming was developed in C language by using Turbo C compiler.